The differential effects of the empty chair dialogue and cognitive restructuring on the resolution of lingering angry feelings. - Soulière, Michelle. (University of Ottawa (Canada), 1994)
This study explored the differential effectiveness of the Gestalt empty chair dialogue and RET cognitive restructuring when applied to the resolution of unfinished business consisting of lingering angry feelings toward a significant other. It was hypothesized that the Gestalt empty chair would be more effective in resolving lingering feelings of anger than RET cognitive restructuring procedures. Four therapists were trained in the application of both interventions and each therapist saw ten clients, five in each condition. The subjects consisted of 40 non distressed women between the ages of 20 to 54 (M = 31.55), who were experiencing unresolved feelings of anger toward a person who had been significant to them in their past, and who were willing to work on this issue during the sessions. Subjects were randomly assigned to the treatment conditions and received two counseling sessions aimed at resolving their angry feelings. A verification of therapist interventions was conducted and each treatment was found to be faithfully implemented. An examination of sample characteristics yielded no significant differences between the subjects in each experimental condition. Post-session measures revealed no significant between-group differences in subjects' perceptions of the degrees of progress and resolution achieved during the sessions, the quality of the sessions, and the helpfulness of the therapist. With respect to post-session therapist measures, no significant between-group differences were found in therapists' perceptions of the degree of resolution achieved during the sessions and their perceptions of the degree to which they understood their clients. Outcome measures were administered before and immediately after treatment, and again one week later. A statistically significant difference was found between the empty chair and cognitive restructuring conditions immediately after treatment on one of the outcome measures. Subjects in the cognitive restructuring group had a significantly less negative perception of their significant other immediately after treatment however, this between-group difference was not maintained at the one-week follow-up. Follow-up testing revealed no significant differences between the two experimental groups. Overall, the results of this study indicated that the empty chair dialogue and cognitive restructuring procedures led to similar results on subject measures of the degree of improvement and discomfort related to the unfinished business, on subject self-reports of the degree of unfinished business resolution achieved, on subjects' perceptions of the quality of the relationship with the significant other, and on subjects' tendency to control angry feelings. These findings appear to suggest that the empty chair dialogue and cognitive restructuring procedures may produce similar results when used to deal with lingering angry feelings toward a significant other. However, other factors which may have influenced the outcome of this study as well as suggestions for further research are presented in the discussion section of this paper.
Keywords: Psychology, Clinical.